UZBEK LANGUAGE TERMINOLOGY IN THE FIELD OF KNIFE-MAKING: THE KNIFE AND ITS PARTS' NAMES - Rakhmatullayev Anaskhon Khamidulloevich (Journals Park Publishing, 2025)
The article contains professional vocabulary, terms of the knife-making sphere in the Uzbek language: opinions on the names of knives and their parts.
Keywords: Language and culture, national language, literary language, professional vocabulary, knife-making, knife-making - knife, razor, dagger, early Paleolithic, cutting weapons, Bronze Age, copper, iron and brass.